COVID-19 DEATHS AMONG THE ELDERLY IN A MUNICIPALITY IN NORTHWESTERN PARANÁ, BETWEEN THE YEARS 2020 AND 2021 - Natália Quevedo dos Santos; Karine Franciele Toldo de Toledo; Sônia Maria Marque Gomes Bertolini (Arquivos do Mudi, 2023)
In December 2019, a new virus called SARS-CoV-2 was identified. The World HealthOrganization (WHO) named the disease caused by the new virus COVID-19 (coronavirusdisease, year 2019), and in March 2020, it was declared a pandemic. Since then, there hasbeen a global effort to produce information in order to unravel the clinical, epidemiological,and prognostic factors of the disease. By identifying the main risk factors, it is possible tocarry out early monitoring of the most vulnerable groups, reducing the chance of unfavorableclinical outcomes. It is a consensus that advanced age is associated with an increase inmorbidity and mortality. This study aimed to verify the occurrence of COVID-19 deathsamong the elderly in the city of Maringá, Paraná, in the years 2020 and 2021, as well as theirassociation with gender. This research is characterized as a retrospective quantitative study.The data were obtained from the Notifiable Diseases Information System (Sinan). Thedependent variable was the occurrence of death in elderly patients, and the independentvariables were gender and year of occurrence. Descriptive and inferential statistics were usedto analyze the data. Results showed that in 2020, there were 514 deaths (40.5% female and59.5% male). In 2021, the number of deaths increased exponentially, reaching 2025 cases(39.6% female and 60.4% male). The highest occurrence of COVID-19 deaths among theelderly occurred in 2021 and in males. Based on this profile, specific strategies and care linesshould be studied for this more vulnerable population in times of pandemics.